2018
DOI: 10.1177/1948550618762298
|View full text |Cite
|
Sign up to set email alerts
|

Motivated Collective Defensiveness: Group Members Prioritize Counterarguing Out-Group Criticism Over Getting Their Work Done

Abstract: Group members defensively reject out-group criticism in self-reports because they perceive it as more threatening than the same criticism from the in-group (intergroup sensitivity effect). But does this effect motivate action? In five experiments, group members exhibited behavior patterns characteristic of motivated goal pursuit: They prioritized defending their group over completing their individual work (Experiments 1-5), even when work was intrinsically rewarding (Experiment 2) or incentivized (Experiment 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(67 citation statements)
references
References 43 publications
5
61
1
Order By: Relevance
“…For example, the critic could make his/ her good intentions explicit or emphasize the opportunity to grow from the criticism. Decreasing defensiveness towards outgroups criticizing is especially needed considering recent research showing that defensiveness can translate into behavioral reactions, for example defending the ingroup or showing hostile actions towards the outgroup (Thürmer & McCrea, 2018;Thürmer et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the critic could make his/ her good intentions explicit or emphasize the opportunity to grow from the criticism. Decreasing defensiveness towards outgroups criticizing is especially needed considering recent research showing that defensiveness can translate into behavioral reactions, for example defending the ingroup or showing hostile actions towards the outgroup (Thürmer & McCrea, 2018;Thürmer et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, recent research demonstrates that being confronted with negative expectations about a group one belongs to (i.e., stereotype threat) may reduce peoples' social approach motivation (Martiny & Nikitin, 2019). Moreover, group members may engage in costly behavioural defences to protect their group against threatening out-group criticism (Thürmer & McCrea, 2018;Thürmer & McCrea, 2021;Thürmer et al, 2019). Future research should investigate how planning can mitigate these defensive responses to collective threats.…”
Section: Limitations and Need For Future Researchmentioning
confidence: 99%
“…(2008) found that outgroup critics are viewed more positively when they combine their criticism with praise of another aspect of the criticized group, or when they acknowledge a similar problem in their own group. In contrast, the ISE is not reduced when the criticism targets only some group members (Hornsey et al., 2008), when the ingroup's identity has been affirmed beforehand (Thürmer et al., 2019), or when the criticism is based on high‐quality arguments (Esposo et al., 2013).…”
Section: Intergroup Sensitivity Effect In Organizational Contextsmentioning
confidence: 99%
“…For example, Thürmer and McCrea (2018) showed in five experiments that critical comments from the outgroup do not only lead to outgroup derogation but also to hostile actions toward outgroup members. Subsequent research showed that criticism from the outgroup leads to counterarguing at the expense of group productivity (Thürmer et al., 2019).…”
Section: Introductionmentioning
confidence: 99%